Learning method innovation: Integrating projects for holistic development of early childhood. - Aliyatuz Zulfa, Nadia; Hibana, Hibana; Sari, Nurita (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background : Innovative learning methods are essential in early childhood education to support their holistic development, encompassing cognitive, social, emotional, and physical aspects. However, the implementation of monotonous learning methods often reduces children's interest in learning. The Project-Based Learning (PjBL) model offers a relevant approach to enhancing children's creativity and collaborative skills.Aim.:This study aims to analyze the implementation of PjBL in improving the creativity and collaboration skills of early childhood learners and to provide practical guidance for educators.Methode:This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation.Result : The findings reveal that the implementation of PjBL through thematic, partial, and occasional approaches is effective in enhancing children's engagement in the learning process. Children demonstrated improved creativity, independence, and collaboration skills. Teachers also played a significant role as facilitators throughout the project implementation process.Conclusion.: This research provides a new contribution by exploring the implementation of PjBL in a local context, specifically in early childhood education in Indonesia. It bridges the gap between theory and practice, which has previously focused more on general applications without emphasizing children's creativity and collaboration. These findings support the development of the Merdeka Curriculum by prioritizing active, collaborative, and contextual learning relevant to the developmental needs of early childhood learners. Thus, PjBL proves to be a relevant learning model, encouraging active exploration, mastery of 21st-century skills, and meaningful learning experiences, while simultaneously serving as a solution to improve the quality of learning aligned with children's developmental needs.